Antimicrobial activity in leaf extract of Neem in broiler - Akhter, Rupaly; Sarker, Md Wadud (Research in Agriculture Livestock and Fisheries, 2019)
The main objective of the study was to evaluate antibacterial activity of Neem leaf extracts (methanolic) against E. coli and Salmonella using different test such as production performances, biochemical, hematological, bacteriological tests and zone of Inhibition (ZOI) method. Azadirachta indica (neem) leaf extract was used to test growth performance, biochemical , hematological parameters and antimicrobial activity against disease causing bacteria Escherichia coli and Salmonella. That’s result indicated, methanolic extract of neem increased body weight, feed conversion ratio, decreased mortality rate from different microbial diseases.it also helped to maintain normal biochemical parameter for better health life of chicken. Neem extract increased leukocyte counts and decreased total viable count of bacteria in cecal faeces. Methanol extracts of varying concentrations 1.0, 1.5, 2.0 and 2.5% was prepared and tested against test organisms using agar diffusion method. Gentamicin of same varying concentrations was used to compare the effect of antimicrobial activity of methanol leaf extract. Data revealed that methanol extract of Neem has shown highest antimicrobial activity. Leaf extract of A. indica (Neem) had exhibited a potent antibacterial activity against various strain (E. coli, Salmonella spp) of bacterial pathogens, it showed almost nearest to microbial activity of gentamycin. Res. Agric., Livest. Fish.6(2): 337-343, August 2019